Tekanan Sosial terhadap Perempuan dalam Film Andai Ibu Tidak Menikah Dengan Ayah Karya Kuntz Agus: Feminisme Naomi Wolf - Nensilianti Nensilianti; Ridwan Ridwan; Cahya Fatira (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study examines the social pressures experienced by women in Kuntz Agus's film "If Mother Didn't Marry Father" using Naomi Wolf's feminist perspective. This study focuses on how the main character, Wulan, experiences various forms of pressure in her family life. The method used is qualitative, with data collection techniques through observation and documentation, obtained from dialogues, scenes, and conflicts in the film. The results show that Wulan faces several forms of social pressure, such as the burden of domestic work, the double burden of household and economic responsibilities, imbalanced roles in the family, emotional stress, and conflict in the household. These various pressures are interrelated and show that women bear more responsibilities than men in the family. Based on Wolf's perspective, this condition occurs because of social constructions that place women in an unequal position through layered role demands. These findings also show that these social pressures not only impact individual women but also affect relationships and harmony within the family; thus, this film reflects the social reality related to gender role inequality in society.